Peningkatan Pengetahuan Keamanan Makanan Jajanan Pada Anak Sekolah Di Kecamatan Ubud Kabupaten Gianyar - I Gusti Putu Sudita Puryana; Ni Putu Agustini; Anak Agung Ngurah Kusumajaya (Poltekkes Kemenkes Denpasar, 2019)
BPOM RI food poisoning data shows that 19% of food poisoning incidents occur in the school environment, of which 78.57% come from snacks for school children, 46% for food for school children are not eligible because they contain hazardous chemicals such as formalin, borax and coloring rhodamine, containing Food Additives, cyclamate, and benzoate which exceeds safe limits and contains microbiological contamination. This community service aims to: 1) increase the knowledge of elementary school children about food safety, 2) Establish food safety cadres in elementary schools in the villages of Sayan and Singakerta. Youth nutrition counseling activities conducted at SDN 1 Sayan, SDN 4 Sayan, SDN 5 Sayan, SDN 2 Singakerta, SDN 3 Singakerta, SDN 4 Singakerta, and SDN 6 Singakerta, Ubud District, Gianyar Regency were attended by 116 students. Each elementary school is represented by 4 students and is accompanied by one teacher. The material delivery method is a lecture with the help of counseling media in the form of powerpoint shows and turning sheets and questions and answers. Counseling activities by forming food safety cadres carried out turned out to bring quite effective results. This is proven by the changes in the results of the pretest and posttest as evaluation material.Keywords: School Children Snack Food, counseling, food safety cadres